The Green Paradox of Corporate Lending Risk in ASEAN-5 Banks - Muizzuddin; Rachmadi, Erfan; Putri, Nyayu Khalilah; Febrianti, Devi (Accounting Department,, 2026)
Purpose - This paper examines whether ESG engagement affects corporate lending risk in ASEAN-5 banks and whether state ownership and bank capital levels moderate this relationship. Design/methodology/approach - Using an unbalanced panel of 34 banks in ASEAN-5 from 2014 to 2023, this study applies random effects regression, interaction models, capital-based heterogeneity analysis, and two-step System GMM. Findings - The findings reveal a selective role of state ownership. While ESG engagement increases corporate lending risk, particularly through the Environmental and Governance pillars, SOE banks reduce the risk effect of Governance-related ESG engagement. This indicates that state control can act as a governance-based stabilizing mechanism, especially when banks face capital constraints. Practical implications - ESG implementation should be integrated into credit risk assessment and prudential supervision, especially for low-capital banks exposed to transition risks. Originality/value - This study departs from the view that ESG engagement and state ownership necessarily reinforce one another. Instead, it shows that the relationship between the two is conditional. State control appears to reduce credit risk only through the Governance pillar, particularly when banks face limited capital. In the ASEAN-5 context, where state ownership continues to hold considerable institutional influence, this pillar-level analysis offers a more nuanced understanding of when state ownership can act as a safeguard for good governance, rather than assuming that such a role is always present. Paper type - Research paper